Are We Late in the Diagnosis of Malignities Occurring in Solid Organ Transplant Patients? 11 Years- Experience - ŞİMŞEK, MELİH; Turkeli, Mehmet; Simsek, MELİH; Aldemir, Mehmet Naci; Yildirim, Nilgun; ÇANKAYA, Erdem; ERDEMCİ, Burak; BİLİCİ, Mehmet; TEKİN, Salim Başol; Arslan, Sukru; KORKUT, Ercan (My University, 2016)
Objective: Our aim is to evaluate the frequency and characteristics of cancer in the population of patients with solid organ transplant who are under immunosuppressive medication. In this study we aimed to emphasize the importance of early diagnosis of cancer in solid organ transplant recipients. An aging population began to receive solid organ transplantation and survival times prolonged. But this had a cost and new problems came forward. Especially de novo cancers because of immunosuppressive therapy took notice. Risk of malignancy increases after organ transplantation and cancer incidence was about 2.3-3.1% in these patients including skin cancer, lung cancer, malign lymphoma, cervix cancer, kaposi sarcoma, and hepatobiliary cancer.